CaMn1−xBxO3−δ (B = Al, V, Fe, Co, and Ni) perovskite based oxygen carriers for chemical looping with oxygen uncoupling (CLOU). (15th July 2016) - Galinsky, Nathan; Sendi, Marwan; Bowers, Lindsay; Li, Fanxing
Highlights: Effects of various B-site dopants for CaMnO3 based oxygen carrier are investigated. Fe-dopants can be effectively incorporated into the CaMnO3 structure. Fe-doped CaMnO3 samples show significant α-oxygen release between 350 and 500 °C. Fe-doped oxygen carriers observe long term redox stability without formation of undesired phases. Fe-doped CaMnO3 exhibits superior activity for Pittsburgh #8 coal char combustion compared to undoped samples. Abstract: Operated under a cyclic redox mode in the presence of an oxygen carrier, the chemical looping with oxygen uncoupling (CLOU) process has the potential to effectively combust solid carbonaceous fuels while capturing CO2 . The overall process is enabled by an oxygen carrier that is capable of reversibly exchanging its lattice oxygen (O 2− ) with gaseous oxygen (O2 ) under varying external oxygen partial pressures ( P O 2 ). As such, further improvements of the CLOU process relies largely on the identification of oxygen carriers with higher activity, better recyclability, and improved resistance toward physical degradation. This article investigates dopant effects on CLOU properties of oxygen carriers with a CaMnO3 parent structure. Various B-site compatible metal cations including Fe, Ni, Co, V, and Al are incorporated into the perovskite. While CaMnO3 suffers from stability issues resulting from irreversible transitions to spinel (CaMn2 O4 ) and Ruddlesden–Popper (Ca2 MnO4 ) structures under typical CLOU redox conditions, a number of B-site doped perovskites exhibited promising phase stability and redox activity. Of the oxygen carriers investigated, Fe-doped CaMnO3 exhibits the most promising CLOU properties while showing high compatibility with the CaMnO3 parent structure. In terms of redox performance, CaMn1− x Fe x O3− δ exhibit notable redox activity at temperatures as low as 600 °C. No deactivation was observed over 100 redox cycles. The doped perovskite structure was also significantly more stable than undoped CaMnO3, showing no signs of decomposition at 1200 °C. When operated under identical conditions, the Fe-doped oxygen carrier is observed to achieve significantly higher conversion of Pittsburgh #8 coal char compared to undoped CaMnO3 oxygen carrier, when operated at 850 °C.